Step 1: Write out the formular for the equation of a circle with the radius and the centre of the circle given.
(x-a)² + (y-b)² = r²
Step 2: Write out the given data
a= 8
b=4
r= radius= 7
Step 3: Substituting the values
![\begin{gathered} (x-8)^2+(y-4)^2=7^2 \\ (x-8)(x-8)+(y-4)(y-4)=49 \\ x(x-8)-8(x-8)+y(y-4)-4(y-4)=49 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/a74aoqzerkra2bt38ktxdiafnun8whqcuc.png)
![\begin{gathered} x^2-8x-8x+64+y^2-4y-4y+16=49 \\ x^2-16x+64+y^2-8y+16=49 \\ \text{Collecting like terms and rearranging} \\ x^2+y^2-16x-8y+64+16-49=0 \\ x^2+y^2-16x-8y+31=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/l0c21rjs6ubfs8mhwlrnge9cx8etkb7br8.png)
Hence the equation of the circle is x²+y²-16x-8y+31=0.